2022
DOI: 10.1111/jam.15238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microecological agents on water environment restoration and microbial community structures of trench system in a Baiyangdian wetland ecosystem

Abstract: Aims To evaluate the effects of periodic application of effective microorganism (EM) bacteria and calcium peroxide on water environment restoration of a trench wetland ecosystem and its impact on microbiota in water and sediment. Methods and Results The EM bacteria and calcium peroxide were alternately sprayed into the trench water, and changes in the physicochemical indices of water and sediment, and in microbiota structure were subsequently investigated. Alternately spraying of calcium peroxide and EM bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Microorganisms are an important part of the ecosystem, and participate in the material cycle and energy flow in nature [ 18 ]. Florfenicol is a broad-spectrum antibiotic that can inhibit a variety of bacteria; therefore, the remaining antibiotics in the environment inevitably impact microorganisms [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms are an important part of the ecosystem, and participate in the material cycle and energy flow in nature [ 18 ]. Florfenicol is a broad-spectrum antibiotic that can inhibit a variety of bacteria; therefore, the remaining antibiotics in the environment inevitably impact microorganisms [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of the pond microbiota in South China concluded that microbial metabolic activity influenced the nitrogen metabolism, the excess nitrogen of water would decrease with the increasing denitrification capacity of microbial communities [30]. Research indicated that the application of low final concentration of EM bacteria and calcium peroxide could improve water quality and significantly reduce total phosphorus, total nitrogen, and NH 4 + -N [31]. The highest removal rate was shown in Z15 × EM, decreased by 87.19% for NH 4 + -N and 30.33% for NO 3 − -N. There was a remarkable EM bacteria effect on the pH and DO of paddy drainage in this study.…”
Section: Nitrogen Removal By Zeolite and Effective Microorganisms (Em)mentioning
confidence: 99%
“…These microbes are vital to the river food web, and changes in their composition can vary temporally, resulting in unintended consequences for river ecosystem health [ 17 ]. Seasonal fluctuations in flow, water temperature (WT), input of inorganic compounds, and suspension and deposition of allochthonous and autochthonous organic materials have the potential to alter the structure of microbial communities in rivers and lakes [ 18 , 19 ], thereby affecting the circulation of geochemical substances and the flow of energy through water microorganisms. By analyzing the correlation between environmental factors and the microbiota in water, the weights of environmental factors can be calculated, potentially increasing the environmental indicative value and objectivity of WQI and WQI min .…”
Section: Introductionmentioning
confidence: 99%